Reflexión crítica sobre la memoria colectiva: integración interdisciplinar, metodologías, tensiones y perspectivas (Raíces: Revista de Ciencias Sociales y Políticas, 2018)
The present article aims to present a critical reflection on collective memory in its multiple dimensions, from interdisciplinary integration, to methodologies, as well as their tensions and perspectives. It recognizes that  memory as a human quality is the product of the reflexivity that is required as part of the approach and distancing in the process of knowledge production. The theoretical basis on the studies of the memory is based on the thought of Walter Benjamin, Maurice Halbwachs, Pierre Nora, Walter Mignolo and Elizabeth Jelin. Likewise, the methodological approach is based on Grounded Theory, theoretical sampling, the use of qualitative techniques and the assurance of science and with the support of quality criteria inspired by Glaser and Strauss, Yin, Lincoln and Guba. The analysis of the data, leads to the creation of interdisciplinary analytical constructs that allows to relate the theory with practice, applied for the creation of coherent strategies that contribute to the dignification of the population that lives, by own experience, each one of the social processes, economic and political processes that give rise to their own memories, analysis and reflections. Finally, it is argued and concluded about the perspectives of the uses of memory in the present and near future, in a context where social processes have generated significant changes in the daily and strategic life of the population.
Keywords: Collective memory, Silence, Forgetfulness, Grounded Theory